Hypertensive Disorders of Pregnancy and the Recent Increase in Obstetric Acute Renal Failure in Canada: Population-based Retrospective Cohort Study. Issue 3 (September 2015) - Mehrabadi, A.; Liu, S.; Bartholomew, S.; Hutcheon, J.A.; Magee, L.A.; Kramer, M.S.; Liston, R.M.; Joseph, K.S.
Abstract : ( BMJ . 2014;349:g4731)